Amplitude Suppression of Nongaussian Sea Clutter in a Coherent Bandpass Path of the Receiver - E. A. Milashchenko; A. A. Yazovsky (Известия высших учебных заведений России: Радиоэлектроника)
The method of non-linear amplitude suppression of radar clutter from a sea surface in the coherent band path of the receiver is considered. The model of the most adequate nongaussian radar clutter from the rough sea surface which envelope is based on K-distribution of density of probability is used. The mathematical model of clutter is considered. For various values of parameters of model of clutter amplitude characteristics of a non-linear element and dependence of coefficient of suppression on the relation a clutter/noise are under construction.